Analisis Konseptual Penetapan Orde Perkotaan dalam Pembangunan Ekonomi Kota - Rusmiati Rusmiati; Thamara Idil Fitri Marliana; Angga Pratama; Feri Kurniawan; Chika Dwi Oktaviani (Jurnal Manajemen, Bisnis dan Kewirausahaan, 2026)
Urban development is inextricably linked to the process of urbanization and its role as a center of economic activity. Each city has a different level and function, necessitating the classification of cities based on their urban order. Determining urban order is crucial for understanding a city's role within the urban system and serves as a basis for more targeted economic development planning. This article aims to analyze the concept of determining urban order and its relationship to urban economic development. The method used is a literature review, examining various theories and research findings related to urban hierarchy, population distribution, and urban economic growth. The study results indicate that determining urban order is generally based on population size, density, service functions, and the city's economic role. Cities with higher levels of order tend to have more complex economic activity and become centers of growth for surrounding areas. Therefore, understanding urban order can assist the government in formulating more equitable and sustainable urban economic development policies.